Banking model and territorial financial inclusion during the Great Recession: a comparative analysis between Social, Cooperative and Commercial Banking - Fernández-Olit, Beatriz (REVESCO. Revista de Estudios Cooperativos, 2020)
This article focuses on the importance of bank branches in the financial inclusion of the territory, regardless of whether the digitalization partly favours the provision of services. Assuming this premise, this paper reviews the factors determining the reduction of bank branches at a provincial level during the most severe period of the Great Recession (2008-2013). Using cluster analysis, the trends of reduction of the branches network are analysed considering the different categories of banking entities. The results indicate that the intense contraction of the saving banks’ branch network was compensated by a partial absorption of branches by commercial banks, which remained in dynamic and urban areas, where also raised the risk of bank discrimination due to socioeconomic inequality. Meanwhile, cooperative banking sustained rural and aging areas, expanding its own network and taking advantage of the empty spaces left by the savings banks. The conclusions reflect on the reasons that have justified the reduction of the branch network, considering the new European regulatory framework, which guarantees citizens access to a bank account and promotes new financial inclusion strategies. Finally, the paper highlight the principles that gave rise to social banking, analysing their applicability in the post-crisis environment.